Metabolism of carbohydrates and activity of the antioxidant system in mosses on a post-technogenic salinized territory - N. Y. Kyyak (Regulatory Mechanisms in Biosystems, 2022)
Adaptive physiological and biochemical reactions of mosses Didymodon rigidulus Hedw., Barbula unguiculata Hedw. and Brachythecium campestre (Müll. Hal.) Schimp. to salt stress have been investigated from the territory of the tailings storage of the Stebnyk Mining and Chemical Enterprise “Polymineral” (Lviv region, Ukraine). The peculiarities of carbohydrate metabolism in mosses under salinity conditions have been studied. The content of soluble carbohydrates and proline, the antioxidant activity, the content of ascorbate and reduced glutathione as well as the activity of enzymes of their metabolism – ascorbate peroxidase and glutathione reductase at the initial stages of the stress (salt shock) and prolonged stress exposure (salt stress) have been evaluated. It has been found that the increase of α-amylase activity, enhancement of the hydrolysis of starch and the increase of the concentration of soluble carbohydrates under salt stress were the reactions of the studied species of mosses. It has been established that there was an increase in the concentration of soluble carbohydrates by 1.2–1.5 times in moss shoots under salinity conditions, compared with plants from the background area (vicinity of Stebnyk). Experimental studies have shown that under salinity conditions sucrose dominates in the pool of soluble carbohydrates (59.0–79.5% of the total sugars content). The sucrose content was 1.5–2.0 times higher in the plants B. unguiculata and D. rigidulus from the highly saline area of the tailings storage. It has been indicated that under stress conditions constitutive adaptive mechanisms are more expressed in resistant moss species, and plants with a lower level of resistance adapt to the stressor, mainly due to induced protective systems. Experimental studies have shown that plants B. unguiculata and D. rigidulus, which are resistant to abiotic stressors, have a high constitutive pool of soluble carbohydrates both at the beginning of the experiment and under prolonged exposure of the salt stress. In the shoots of the sensitive moss B. campestre the stress-induced character of the sugars accumulation has been revealed. The accumulation of proline in mosses cells under salt stress depended on their species characteristics. The stress-induced accumulation of proline can be considered as a part of the bryophytes’ protective system, but this osmolyte does not play a key role in the formation of the mosses’ resistance to salt stress. Obviously, soluble carbohydrates are the main osmolytes in the moss cells. It has been found that resistant moss species have a high constitutive antioxidant status, while in the sensitive moss B. campestre the increase in the antioxidant activity occurred during prolonged salt stress, which may indicate its induced nature. It has been shown that the resistant mosses B. unguiculata and D. rigidulus have 3–4 times higher levels of glutathione and ascorbate content and 1.6–2.5 times higher activity of enzymes of their metabolism – glutathione reductase and ascorbate peroxidase, compared to plants of the less tolerant moss species B. campestre, which provided reduction of the lipid peroxidation process in plasma membranes and decreased the content of TBA-active products under stress.